LITERASI SEJARAH DALAM KARYA SASTRA ANAK DAN PERANANNYA DALAM PENDIDIKAN - Reza Aristiawan (Journal of Linguistics, Literature, Culture and History, 2025)
Historical literacy is crucial for building national identity and character from an early age. Historical literacy helps individuals recognize the cultural roots, values, and struggles of previous generations, thereby fostering a sense of belonging and pride in the nation's heritage. This study explores the role of historical literacy in children's literature and its relevance to character education, nationalism, and historical knowledge. It aims to enrich the study of children's literature and history education, as well as provide guidance for teachers, parents, and children's literature writers. This study uses a qualitative approach with library research to explore historical literacy and the role of children's literature in history learning. The study found that children exposed to historical stories from an early age demonstrate a sense of belonging to their cultural heritage and pride in national heroes and important events. Historical literacy in children's literature is crucial for shaping identity, nationalism, morality, and critical thinking from an early age. Historical literacy not only conveys knowledge about past events but also explores their meaning, relevance, and values, thereby fostering strong character and national awareness.